Biosocial perspectives on children (Cambridge University Press, 1998)
Childhood is a uniquely human life-stage, and is both a biological phenomenon and a social construct. Research on children is currently of wide-ranging interest. This groundbreaking book presents reviews of childhood from four major areas of interest--human evolution, sociology/social anthropology, biomedical anthropology and developmental psychology--to form a biosocial, cross-cultural understanding of childhood. The book places a strong emphasis on how childhood varies from culture to culture, offering examples from developed and developing countries, as well as from other animal species. It will be of interest to students and scholars within the fields of human biology, anthropology, sociology, health studies, and developmental psychology